A corpus-based analysis of light verb constructions with MAKE and DO in British English - Giparaitė, Judita (Kalbotyra, 2024)
The comparison of light verb constructions with the verbs make and do has not received much attention. The present paper is an attempt to contribute to the study of these constructions. It aims to analyze the light verbs make and do in combination with the same deverbal nouns to identify similarities and differences between the two light verbs and examine the contribution of the light verbs and deverbal nouns to the light verb construction in terms of semantic and syntactic features. The research is corpus-based, and the data for analysis are collected from the British National Corpus (BNC). The semantic description deals with characteristics such as generality, polysemy and aspectual meaning, and the syntactic description focuses on complementation. The analysis of findings demonstrates that, despite some similarities, almost all constructions with the two light verbs show either meaning or/and complementation differences. The study also reveals that both light verbs and deverbal nouns have an impact on the semantics and syntax of the construction. Light verbs may affect light verb constructions semantically in terms of generality and polysemy, and the aspectual meaning of constructions depends on both light verbs and deverbal nouns. Likewise, both light verbs and deverbal nouns have an influence on complementation, but in their own way: light verbs on the selection of complements and deverbal nouns on complementation patterns.